2011
DOI: 10.1149/1.3655433
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Activity of Non-Stoichiometric Perovskites toward Oxygen Reduction Reaction in Alkaline Electrolytes

Abstract: Perovskite La x Ca 0.4 MnO 3 (x = 0.4, 0.5, 0.6) powder was prepared through a sol-gel method and characterized by X-ray diffraction (XRD), a gas adsorption technique (BET) and transmission electron microscopy (TEM). The electrocatalytic properties of La x Ca 0.4 MnO 3 /C composites towards the oxygen reduction reaction (ORR) were studied using rotating ring-disk electrode (RRDE) techniques and Koutecky-Levich theory in both 1 M and 6 M KOH electrolytes. The results show better ORR activities for non-stoichiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…DnormalO2 is the diffusion coefficient of oxygen in the electrolyte, while CnormalO2 is the concentration of the dissolved oxygen in the electrolyte at partial pressure of 1 atm. D 0 , C 0 , and v in 1 m KOH is about 1.65 × 10 −5 cm 2 s −1 , 8.3 × 10 −7 mol cm −3 , and 9.5 × 10 −3 cm 2 s −1 , respectively …”
Section: Methodsmentioning
confidence: 90%
“…DnormalO2 is the diffusion coefficient of oxygen in the electrolyte, while CnormalO2 is the concentration of the dissolved oxygen in the electrolyte at partial pressure of 1 atm. D 0 , C 0 , and v in 1 m KOH is about 1.65 × 10 −5 cm 2 s −1 , 8.3 × 10 −7 mol cm −3 , and 9.5 × 10 −3 cm 2 s −1 , respectively …”
Section: Methodsmentioning
confidence: 90%
“…Partial substituting La (3+) with an alkaline earth element (Ca 2+ or Sr 2+ ) or a lanthanide with a different valence (Ce 4+ ) at the A site introduces oxygen nonstoichiometry into the perovskite structure, leading to an improved oxygen mobility. ,,, Owing to the matched atomic size, strontium (Sr) is commonly doped with La on the A site, forming a La 1– x Sr x MO 3 (M = Fe, Co, Mn) type of structure. The substitution of La (3 + ) with divalent Sr (2 + ) results in cation vacancies and the formation of high-valence M cations to facilitate oxygen and electron transfer, making this structure a promising candidate for catalyzing ORR in alkaline media . Tulloch et al reported that Sr-dependent ORR performance in 1 M KOH with La 0.4 Sr 0.6 MnO 3 achieved the highest activity among all the La 1– x Sr x MnO 3 compounds (LSMOs) studied .…”
Section: La-based Perovskites As Electrocatalysts For Oxygen Reductio...mentioning
confidence: 99%
“…Recently, Shao-Horn et al experimentally identified the charge-transfer energy, the relative energies of transition-metal (TM) 3d and O 2p valence electronic states, as a key electronic descriptor that interrelates the bulk electronic structure and surface properties of many perovskite oxides. Sunarso et al and Zhu et al illustrated that LaCoO 3 exhibited better catalytic activity and rechargeable stability as a catalyst for metal–air batteries. , Gyenge et al reported that MnO 2 –LaCoO 3 mixed materials have a synergistic catalytic effect toward the ORR and OER, and the insertion of potassium is beneficial in decreasing the overpotentials. , There are two obvious advantages for A-site partial substitution with low-valence metal ions, leading to increasing oxygen vacancies and the proportion of the B-site transition-metal ions to unstable oxidation states (B 3+ /B 4+ redox couple). , Xu et al prepared porous La 0.75 Sr 0.25 MnO 3 nanotubes with high surface area via an electrospinning technique; they reported that the La 0.75 Sr 0.25 MnO 3 nanotubes can improve long cycling life and lower the overvoltage of lithium–oxygen batteries . Since the B site is commonly considered as the active site, the substitution of the B site with a large amount of other ions with redox couples can enhance oxygen mobility. , Moreover, in comparison to nanoparticle or two-dimensional (2D) platelet morphology, nanofibers with a high aspect ratio and porosity usually show superior performance for the ORR/OER reaction since they can maximize the catalytic sites and facilitate the diffusion of electrons and reactants …”
Section: Introductionmentioning
confidence: 95%
“…34,35 There are two obvious advantages for A-site partial substitution with low-valence metal ions, leading to increasing oxygen vacancies and the proportion of the B-site transition-metal ions to unstable oxidation states (B 3+ /B 4+ redox couple). 36,37 Xu et al prepared porous La 0.75 Sr 0.25 MnO 3 nanotubes with high surface area via an electrospinning technique; they reported that the La 0.75 Sr 0.25 MnO 3 nanotubes can improve long cycling life and lower the overvoltage of lithium−oxygen batteries. 38 Since the B site is commonly considered as the active site, the substitution of the B site with a large amount of other ions with redox couples can enhance oxygen mobility.…”
Section: ■ Introductionmentioning
confidence: 99%